1996
DOI: 10.1002/(sici)1099-0518(199602)34:3<367::aid-pola5>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Radical copolymerization ofN-alkylmaleimides with isobutene and the properties of the resulting alternating copolymers

Abstract: Radical copolymerization of N‐methylmaleimide (MeMI) as well as other N‐alkylmaleimides (RMI) and isobutene (IB) was carried out with 2,2′‐azobis(isobutyronitrile) as an initiator at 60°C. The initial rate of the copolymerization (Rp) was dependent on the monomer composition and was maximum at the 40 mol % of MeMI in the feed. A solvent effect on the Rp and the monomer reactivity ratio was observed in this copolymerization system, i.e., copolymerization in chloroform produced a higher Rp and an alternating ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
48
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 0 publications
4
48
0
Order By: Relevance
“…[28][29][30] Considering a steric factor, poly(2-alt-IB) was expected to show the highest T g value due to the steric hindrance, but actually this was not true. In a previous paper, 18 the T g values of poly(XPhMI-alt-IB) containing 2-methyl and 2,6-dimethyl substituents in the Nphenyl group were reported to be 207 and 237 C, respectively. The T g value (222 C) for poly(2-alt-IB) in the present study was higher than that of the 2-methyl-substituted one.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…[28][29][30] Considering a steric factor, poly(2-alt-IB) was expected to show the highest T g value due to the steric hindrance, but actually this was not true. In a previous paper, 18 the T g values of poly(XPhMI-alt-IB) containing 2-methyl and 2,6-dimethyl substituents in the Nphenyl group were reported to be 207 and 237 C, respectively. The T g value (222 C) for poly(2-alt-IB) in the present study was higher than that of the 2-methyl-substituted one.…”
Section: Resultsmentioning
confidence: 92%
“…The alternating repeating structure of the copolymers was confirmed by 1 H NMR spectroscopy (Figure 1), similar to the results for the copolymerization of N-alkyl-and N-(alkyl-substituted phenyl)maleimides with IB. 13,18 The steric hindrance of the substituents in the ortho-substituted XPhMIs decreases their propagation rate constants and relative monomer reactivity during homo-and copolymerizations, respectively, according to the number and size of the substituents. 14,26,27 Consequently, alternating copolymers are readily produced during the copolymerization of the ortho-substituted XPhMIs with IB because of a lack of the homopolymerizability of IB.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicated that the AAB-type sequence was predominantly produced during the copolymerization of the RMIs with bulky DIB under the penultimate unit control, [17][18][19] being different from the formation of alternating copolymers with isobutene under terminal control. [11][12][13] The AMI content varied in a range of 12-43 mol% in the copolymers. The carbon-to-carbon double bond of the maleimide ring had a reactivity 10 3 times higher than that of the allyl moiety in the side group, resulting in the selective participation of the maleimide double bonds in propagation during the copolymerization.…”
Section: Resultsmentioning
confidence: 99%
“…[7][8][9][10][11] Especially, the copolymerization of the RMIs with isobutene provided an alternating copolymer with excellent thermal stability, high transparency, and high modulus and strength. [12,13] The introduction of polar groups and cyclic structures into the olefin repeating units led to further increases in their thermally stability and the T g values. [14][15][16] Recently, we demonstrated that the copolymerization of the RMIs provided copolymers with finely controlled structures in the 1:1 alternating and 2:1 sequence-controlled fashions, depending on the steric bulkiness and conjugated structure of olefin and styrene derivatives.…”
Section: Introductionmentioning
confidence: 99%